Associations between cardiorespiratory fitness, physical activity, intraindividual variability in behavior, and cingulate cortex in younger adults - João Bento-Torres; Natáli Valim Oliver Bento-Torres; Chelsea M. Stillman; George A. Grove, Jr; Haiqing Huang; Fatma Uyar; Jennifer C. Watt; Mariegold E. Wollam; Kirk I. Erickson (Elsevier, 2019)
ABSTRACT: Background: Higher levels of cardiorespiratory fitness (CRF) and greater amounts of physical activity have been associated with lower intraindividual variability (IIV) in executive function in children and older adults. In the present study, we examined whether CRF, measured as maximal oxygen uptake (VO2max), and daily volume of moderate-to-vigorous intensity physical activity (MVPA) were associated with IIV of reaction time during performance of the incongruent condition of the Stroop task in younger adults. Further, we examined whether the thickness of the cingulate cortex was associated with regulating variability in reaction time performance in the context of CRF or physical activity. Methods: CRF (measured as VO2max), accelerometry-measured MVPA, Stroop performance, and thickness of the rostral anterior cingulate cortex (rACC) derived from magnetic resonance imaging data were collected in 48 younger adults (age = 24.58 ± 4.95 years, mean ± SD). Multiple regression was used to test associations between IIV during the Stroop task and CRF, MVPA, and rACC thickness. Mediation was tested using maximum likelihood estimation with bootstrapping. Results: Consistent with our predictions, higher VO2max was associated with greater rACC thickness for the right hemisphere and greater daily amounts of MVPA were associated with greater rACC thickness for both the left and right hemispheres. Greater thickness of the right rACC was associated with lower IIV for the incongruent condition of the Stroop task. CRF and MVPA were not directly associated with IIV. However, we did find that IIV and both CRF and MVPA were indirectly associated via the thickness of the right rACC. Conclusion: These results indicate that higher CRF and greater daily volume of MVPA may be associated with lower IIV during the Stroop task via structural integrity of the rACC. Randomized controlled trials of MVPA would provide crucial information about the causal relations between these variables. Keywords: Accelerometry, Aerobic fitness, Cognition, Executive control, Within-person fluctuations